Implementasi Ajaran Trilogi Kepemimpinan melalui Pembelajaran Pendidikan Kewarganegaraan di SD Negeri 01 Tawangmangu Karanganyar - Nadziroh; Wachid Pratomo; Chairiyah (Jurnal Ilmiah Profesi Guru (JIPG), 2020)
The  results  showed  that  (1)  the  implementation  of  the  Leadership  Trilogyteachings  was  applied  by  giving  examples,  awards,  and  peer  tutors  in  learning,  instilling cooperative  attitude,  giving  moral  encouragement  or  direction  to  students  by  teaching rights and obligations as citizens and setting examples or giving good examples, and give a model of an example as a good citizen and always motivate students to be good citizens. (2) Values implemented in Civics Learning are   independent values, discipline, self-confidence, mutual respect, respect for opinions, tolerance, character, and courtesy. The value of honesty, responsibility, vision of leadership, and example is implanted in students.(3)The obstacles to the implementation of the trilogy of leadership are students' different abilities in understanding the material taught by the teacher, memorizing the material, and difficult  in  distinguishing  activities  carried  out  in  accordance  with  learning  values. Students only act and behave naturally, but have not been able to distinguish the values of these  actions.  Students  do  not  understand  the  values  in  learning  and  the  difficult  in applying these values in learning activities in the classroom or in everyday life.